Increasing Poetry Comprehension Skills Through Social-Emotional Learning Elements With Problem Based Learning Model in Class IV - Pratiwi, Veronika Unun; Zakiyyah, Hana; Antana, Agus Sri (Papanda Publisher, 2025)
Low poetry comprehension and limited emotional engagement among elementary students remain persistent challenges in Indonesian language instruction. This classroom action research aimed to improve students' poetry comprehension and social-emotional skills through the integration of Social Emotional Learning (SEL) elements within the Problem Based Learning (PBL) model. The study was conducted in two cycles involving 24 fourth-grade students at SDN Pengkol 01, Sukoharjo. The research applied the Kemmis and McTaggart spiral model, which includes the stages of planning, acting, observing, and reflecting. Data were collected through observation sheets and written tests and analyzed using percentage techniques for completeness criteria. The results from the pre-cycle showed that only 8 students (37.88%) achieved the minimum score of 70. In cycle I, the average score increased to 70.16 with 13 students (59.02%) achieving completeness. However, the criteria for classical completeness (70%) had not yet been fulfilled. In cycle II, after improvements in learning strategies and the reinforcement of SEL components—such as self-awareness, social awareness, and relationship skills—students' performance significantly improved. The class average reached 95.75 with 22 students (94%) achieving completeness. The study concludes that integrating SEL into PBL in poetry learning not only enhances cognitive outcomes but also fosters students' emotional intelligence and interpersonal skills. This approach contributes to more meaningful and holistic learning in the Indonesian language curriculum. The success indicators being met in both cognitive and affective domains confirm the effectiveness of this integrated model for primary school poetry instruction.